Current concepts in organic acidurias: understanding intra‐ and extracerebral disease manifestation. Issue 4 (20th March 2013) - Kölker, Stefan; Burgard, Peter; Sauer, Sven W.; Okun, Jürgen G.
Abstract: This review focuses on the pathophysiology of organic acidurias (OADs), in particular, OADs caused by deficient amino acid metabolism. OADs are termed classical if patients present with acute metabolic decompensation and multiorgan dysfunction or cerebral if patients predominantly present with neurological symptoms but without metabolic crises. In both groups, however, the brain is the major target. The high energy demand of the brain, the gate‐keeping function of the blood–brain barrier, a high lipid content, vulnerable neuronal subpopulations, and glutamatergic neurotransmission all make the brain particularly vulnerable against mitochondrial dysfunction, oxidative stress, and excitotoxicity. In fact, toxic metabolites in OADs are thought to cause secondary impairment of energy metabolism; some of these toxic metabolites are trapped in the brain. In contrast to cerebral OADs, patients with classical OADs have an increased risk of multiorgan dysfunction. The lack of the anaplerotic propionate pathway, synergistic inhibition of energy metabolism by toxic metabolites, and multiple oxidative phosphorylation (OXPHOS) deficiency may best explain the involvement of organs with a high energy demand. Intriguingly, late‐onset organ dysfunction may manifest even under metabolically stable conditions. This might be explained by chronic mitochondrial DNA depletion, increased production of reactive oxygen species, and altered gene expression due to histone modification. In conclusion, pathomechanisms underlying the acute disease manifestation in OADs, with a particular focus on the brain, are partially understood. More work is required to predict the risk and to elucidate the mechanism of late‐onset organ dysfunction, extracerebral disease manifestation, and tumorigenesis.